Monitoring For Good Governance in South Africa: The Complex of a Fair Public Administration: Array - Piet Sebola, Mokoko (Acta Universitatis Danubius. Administratio, 2021)
Post-apartheid South African government came up with stringent measures of ensuring the notion of good governance. This notion is to be achieved through a system that is fair and characterized by elements of transparency. The major purpose is to ensure that public resources are utilized to the benefit of the South African citizens, hence the delivery of services to the recipients. These measures exist in line with established state institutions to monitor compliance and efficiency of the government administration. As way of promoting such notion and strengthening good governance through performance of state Departments, the post-Mbeki administration introduced new government Departments as well as the establishment of the new unit in the Presidency called the Department of Planning, Monitoring and Evaluation (DPME). The unit has been in existence for some years now. State Departments and municipalities in the country continue to get qualified audit reports and adverse audit opinions from the Auditor- General of South Africa (AGSA). This is despite the existence of measures (accountability and ethical practices) and institutions of ensuring good governance and transparency in the country. This article investigates the roles of the South African institutions in monitoring good governance and the extent at which these institutions experience functional limitations to fulfill their constitutional mandate. The argument is that there are inconsistencies between the institutions of monitoring and the real complex public administration environment which involves the institutions, politicians, and public officials.